Fine Motor Development In Toddlers - Satriyandari, Yekti; Dulasdi, Nur Ain Desta (Prosiding University Research Colloquium, 2022)
The degree of children health reflects the health of the nation because children as the successor to thenation have the ability to be developed in continuing development of the nation. The problem is thatnot all children get through the process of development properly. Their developmental are delayed dueto the lack of parents’ recognition of the danger signs (redflag) in their children development, earlydetection checks or development screening in children, and direct involvement of parents in theirchildren world or stimulation from non-parents. The purpose of this study is to see the development ofchildren aged 1-5 years. This type of quantitative. The sampling technique used in this study was nonprobability sampling method called purposive sampling and was calculated by the number of samplesin this study as 50 people. The analysis was carried out using univariate analysis. The results showedthat the description of motoric development of children aged 1-5 years in the Jowah V Maternal HealthUnit, most of the measurement of children development were normal with fine motor development as94.2% of toddler development who had untestable categories of 3 children with a percentage of 5.8%,Jowah V Maternal Health Unit needs to establish cooperation with health workers / health agenciesfor routine children development checks / DDST II so that mothers of toddlers know about theirchildren development regularly.